THE EFFECT OF TRANSFER PRICING, TAX INCENTIVES, THIN CAPITALIZATION, ON TAX AGGRESSIVENESS WITH COMPANY SIZE AS A MODERATE VARIABLE - Agus Ismaya Hasanudin; M Habibi Rizqullah; Denny Susanto (Indonesian Journal of Multidisciplinary Science, 2022)
This study aims to determine the effect of transfer pricing, tax incentives and thin capitalization on tax aggressiveness with firm size as a moderating variable. The object of research used is all manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017-2019. This research is a type of quantitative research with secondary data based on the company's financial statements obtained from the Indonesia Stock Exchange website. The sample selection in this study used a purposive sampling method so that the sample that met the criteria was obtained by 73 companies. Data processing was carried out using the SPSS 25 application program with the research model using multiple linear regression and moderated regression analysis (MRA). The results of the research simultaneously show that the transfer pricing, tax incentives, and thin capitalization variables together have an effect on tax aggressiveness. The results partially show that transfer pricing has no positive effect on tax aggressiveness, tax incentives and thin capitalization have a positive and significant effect on tax aggressiveness. While the moderated regression analysis (MRA) test shows that the firm size variable cannot moderate the effect of transfer pricing and tax incentives on tax aggressiveness, however the firm size variable can moderate and strengthen the effect of thin capitalization on tax aggressiveness.